Arthroscopic Excision for Intra-Articular Osteoid Osteoma of the Olecranon Fossa: A Case Report and Literature Review. (7th July 2020) - Yano, Koichi; Kaneshiro, Yasunori; Sakanaka, Hideki
Abstract : Intra-articular osteoid osteoma (OO) of the elbow is rare. We report a 26-year-old man who presented with pain, swelling, and limited elbow range of motion. Plain computed tomography (CT) showed a radiolucent round lesion at the distal humerus and reactive bone in the olecranon fossa. Conservative treatment with salicylate failed under the suspicion of OO. During elbow arthroscopy, a red solitary lesion was noted after resection of the white reactive bone in the olecranon fossa and was excised en bloc using a bony chisel. Histological examination showed OO. The patient's symptoms resolved the day after surgery. The patient remained asymptomatic 2 years postoperatively. This case report shows the successful clinical results of an arthroscopic procedure for intra-articular OO based on two primary goals: precise location of the lesion indicated by reactive bone on preoperative CT and histological verification using bony chisel.